Implementation of FPGA in Index Data Storage as A Database - Wahyu Wibowo, Ferry; ., . (International Journal of Engineering and Technology, 2018)
Nowadays, the database applications have been built on the top of file systems. Although this system is very tough it has a side that should be aware and concerned. If the database doesnâ€™t manage well it will cause some problems i.e. data redundancy and inconsistency, difficult to access data, data isolation, and integrity problems. The data inconsistency could be emerged by duplication of information from one or many different files or multiple file formats. the hardware-based implementation provides benefits in modifying and reconfiguring, meanwhile, the acceleration using this approaching has a good performance than software-based. In major cases, both of them using a bridge to connect each other which is called co-hardware/software.Â Â